Enhanced sensitivity of 17-α-ethinylestradiol (EE2) detection using carbon quantum dots-integrated tapered optical fiber - Hamid, Rosyati; Mustapha Kamil, Yasmin; Aris, Ahmad Zaharin; Abu Bakar, Muhammad Hafiz; Suhailin, Fariza Hanim; Alresheedi, Mohammed Thamer; Ng, Eng Khoon; Mahdi, Mohd Adzir (Multidisciplinary Digital Publishing Institute, 2025)
In this study, we developed a tapered optical fiber sensor enhanced with carbon quantum dots (CQDs) for the detection of 17-α-ethinylestradiol (EE2). The sensor operates on the changes in refractive index induced by the interaction between EE2 and antibodies on its surface. The incorporation of CQDs significantly increased the available surface area for receptor–analyte interactions, leading to enhanced sensor performance. The sensor demonstrated high sensitivity of 2.4925 nm/(ng/L) within a detection range of 1 to 10 ng/L, with a strong correlation coefficient (R2 = 0.998). A detection limit as low as 0.0426 ng/L (0.144 pM) was achieved, along with a low dissociation constant of 2.19 × 10−11 M as determined by the Langmuir isotherm model. These findings highlight the potential of the CQD-functionalized optical fiber sensors as a promising tool for sensitive and selective EE2 detection in environmental monitoring applications.